2014
DOI: 10.1590/1809-4503201400040008
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to control syphilis and HIV vertical transmission in the health care system in the city of Sao Paulo

Abstract: The difficulties in the reference and counter-reference system of these women and their babies are evident barriers to control the vertical transmission of these infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
2
18

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 12 publications
0
10
2
18
Order By: Relevance
“…An attitude of disbelief regarding the results of a protocol may affect the motivation of the professionals to adopt it, constituting a barrier to its implementation . Poor knowledge of the epidemiological profile of syphilis and CS was also observed in studies performed in São Paulo/Brazil and in Burkina Faso . The high adherence to syphilis in pregnancy case reporting found in this study, superior to that reported by other authors, suggests little cooperation between health surveillance programmes and health care services in the city of Teresina, as the professionals showed insufficient knowledge of the epidemiological profile of CS.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…An attitude of disbelief regarding the results of a protocol may affect the motivation of the professionals to adopt it, constituting a barrier to its implementation . Poor knowledge of the epidemiological profile of syphilis and CS was also observed in studies performed in São Paulo/Brazil and in Burkina Faso . The high adherence to syphilis in pregnancy case reporting found in this study, superior to that reported by other authors, suggests little cooperation between health surveillance programmes and health care services in the city of Teresina, as the professionals showed insufficient knowledge of the epidemiological profile of CS.…”
Section: Discussioncontrasting
confidence: 63%
“…Poor knowledge of the epidemiological profile of syphilis and CS was also observed in studies performed in São Paulo/Brazil and in Burkina Faso . The high adherence to syphilis in pregnancy case reporting found in this study, superior to that reported by other authors, suggests little cooperation between health surveillance programmes and health care services in the city of Teresina, as the professionals showed insufficient knowledge of the epidemiological profile of CS. The return of epidemiological information to the health care providers is fundamental to the health surveillance process.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Em São Paulo, em hospital universitário, falhas nos fluxos de referência e de atendimento foram identificadas, sendo menores para o HIV do que para a sífilis 22 .…”
Section: Discussionunclassified
“…Parallel to the growth of cases of human immunodeficiency virus (HIV) infection among heterosexual individuals, the contamination of women of reproductive age has also increased. Thus, public health authorities began to pay closer attention to the rates of mother to fetus transmission of the virus from (vertical transmission) 1,2 , from one of three routes: the gestational period, labor or breastfeeding 3,4 .…”
mentioning
confidence: 99%